Modulation transfer function analysis in myopic model eye - Othman, Shah Farez; Tamchek, Nizam; Muhammad, Farah Diana; Ithnin, Mohd. Hafidz (The Academy of Sciences Malaysia, 2021)
Hitherto, the eye modelling is based on the emmetropic eye taken its ocular optical components value from the population-based studies. However, no studies have been done to study the effect of aberration of myopic refractive error by modelling the eye using the parameters from ocular biometrics and ray tracing method. This study aimed to determine the modulation transfer function (MTF) of myopic refractive error using eye modelling and ray tracing technique. Three eye models had been successfully modelled in Zemax software, namely, emmetropic Liou and Brennan, myopic Liou and Brennan, corrected myopic Liou and Brennan. The optical performance of the eye models were tested using the MTF. From the MTF analysis at 100 cycles/mm, the MTF value of both tangential and sagittal rays for myopic Liou and Brennan eye was the lowest compared to its emmetropic model. Also, the MTF value of the corrected myopic Liou and Brennan model was higher compared to the uncorrected myopic model. However, the corrected myopic model produced lower MTF values for both tangential and sagittal MTF compared with the emmetropic model of Liou and Brennan. In this study, the accuracy of the MTF for myopia correction and emmetropia were calculated. It was found that the accuracy of the MTF value for corrected myopia at tangential and sagittal rays was lower.